Effects of Exercise on Physical Performances among Frail Older Adults: A Review Study - Prakobchai, Sattha; Pongkiatchai, Rungnapa; Wongwiseskul, Sresuda (Journal of Food Health and Bioenvironmental Science, 2023)
Frailty is a crucial concept in determining physiological reverses among older adults. Physical frailty can predict the vulnerability for community- dwelling older adults as the functional performance declines. Recently, nurses and health care professionals have implemented the strategies to enhance physical capacity among frail older adults. Even the clinical guidelines of physical activity and exercise recommendations are widely published, older adults still engage in a low level of physical exercise. It is notable that exercise intervention is effective way to prevent frailty. This review indicates that a combination of aerobic, resistance exercise, and multicomponent exercise can improve physical performance such as increase muscle strength, balance, muscle mass, gait speed and prevent falls. Frailty is a reversible condition. Therefore, encouraging older adults to perform physical exercise is needed to maintain physical functioning as well as promote quality of life. Nurses play a significant role in frailty recovering both in hospitals and in aged care facilities.